Transforming Growth Factor-β1 Triggers Hepatocellular Carcinoma Invasiveness via α3β1 Integrin - Giannelli, Gianluigi (American Society for Investigative Pathology, 2002)
Metastasis occurrence in the course of hepatocellular carcinoma (HCC) severely affects prognosis and survival. We have shown that HCC invasive cells express α3β1-integrin whereas noninvasive cells do not. Here we show that transforming growth factor (TGF)-β1 stimulates α3-integrin expression at a transcriptional level in noninvasive HCC cells, causing transformation into a motile and invasive phenotype. Such activities are inhibited by neutralizing anti-α3- but not anti-α6-integrin monoclonal antibodies. HCC invasive cells secrete abundant levels of active TGF-β1 in comparison with noninvasive cells, but in the latter, addition of active matrix metalloproteinases-2 increases the concentration of active TGF-β1. In this way, the cells express α3-integrin at a transcriptional level and acquire motility on Ln-5. By contrast, an anti-TGF-β1-neutralizing antibody reduces α3-integrin expression and the invasive ability of HCC invading cells. In HCC patients, TGF-β1 serum concentrations and α3-integrin expression are strongly correlated. The integrin, absent in normal and peritumoral liver parenchyma, is abundantly expressed in HCC primary and metastatic tissue. In particular, patients with metastasis show higher levels of TGF-β1 serum concentrations and stronger expression of TGF-β1 and α3-integrin in HCC tissues. In conclusion, TGF-β1 may play an important role in HCC invasiveness by stimulating α3-integrin expression, and could therefore be an important target for new therapies.